THE DEVELOPMENT AND EVALUATION OF THE QUALITIES OF THINKING SKILLS MODULE - Kiong, Tee Tze; Azman, Mohamed Nor Azhari; Md Yunos, Jailani; Heong, Yee Mei; Mohamad, Mimi Mohaffyza; Mohamad, Baharom; Othman, Widad (Journal of Technical Education and Training, 2013)
Using self-instructional modules could be an alternative approach and make significant contributions to teaching and learning. Module is a planned series of learning activities designed carefully to assist the learners to accomplish certain specific objectives based on individual differences, interest and capability on learning. An attempt to develop and implement a modular approach on teaching thinking skills was made in the secondary school. This paper will discuss various components of this modular approach by referring to Meyer Model. Fleiss’s Kappa was used to determine the degree to which consensus agreement ratings vary from the rate expected by chance, with values greater than .60 indicating substantial non-chance agreement. Fleiss’s Kappa for the inter-rater reliability score was κ = .6357, S.E. = .0990, 95% C.I. = .4416 to .8298, which can be taken to represent constant agreement among three raters for the instrument “Rating scale for the qualities of a module”. The internal-consistency reliability value for the instrument “What you thought of the module” was α = .89 based on 38 students. Analysis on the qualities’ evaluation revealed that eight raters showed an agreement on satisfactory level and above for all 34 items. Meanwhile, 36 students gave positive feedbacks on the format and content of the module.